Some Physiological Studies on Ornamental Ipomora Batatas as a Groundcover Species - Othman, Noriah (1991)
The morphological development and some physiological aspects were studied on two cultivars of sweet potato which are normally used as an ornamental plant. Among the studies under taken were those on the botanical characteristics of the plants, effects of shade and fertilizer and nutrient uptake. The cultivar examined were Imelda and an unnamed 'variegated' type. The effects of shading and fertilizer levels showed growth of the 'variegated' cultivar were severely reduced in heavy shading (70% and 80%). Increasing shade levels increased leaf area ratio (LAR) and leaf area to leaf weight (LALW), but decreased dry matter production, visible quality, chlorophyll content and elemental composition in the leaf tissue. However, fertilizer levels were less effective than shade in altering the parameters above. As shade level sincreased, the content of nitrogen, phosphorus, potassium, calcium and magnesium in the leaves increased.